DengueMG: Um Dashboard Interativo para o Monitoramento de Dengue em Minas Gerais - Silva, Jean Pierre Dias da; Souza, Fernanda Sumika H.; Ferreira, Carlos Henrique Gomes; Freitas, Vander L. S. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Dengue remains a major public health challenge in Minas Gerais, demanding effective and accessible monitoring tools. This work presents DengueMG, an interactive dashboard developed using data from the InfoDengue API, initially focused on Minas Gerais. Informed by a review of epidemiological dashboards, the tool integrates a thematic map with case distribution, alert levels, and incidence rates, along with weekly, monthly, and yearly indicators, bar and line charts, and a quick search interface. Compared to the InfoDengue dashboard, it offers significantly faster response times, improved interactivity, and colorblind-friendly visualizations. Designed to be responsive and user-centered, the dashboard supports data-driven decision-making by policymakers, researchers, and citizens, with potential for replication in other regions and diseases.